Immediate breast reconstruction following mastectomy in pregnant women with breast cancer. Issue 2 (8th July 2016) - Caragacianu, Diana L.; Mayer, Erica L.; Chun, Yoon S.; Caterson, Stephanie; Bellon, Jennifer R.; Wong, Julia S.; Troyan, Susan; Rhei, Esther; Dominici, Laura S.; Economy, Katherine E.; Tung, Nadine M.; Schapira, Lidia; et al.
Abstract : Background: Surgical management of breast cancer in pregnancy (BCP) requires balancing benefits of therapy with potential risks to the developing fetus. Minimal data describe outcomes after mastectomy with immediate breast reconstruction (IR) in pregnant patients. Methods: Retrospective review was performed of patients who underwent IR after mastectomy within a BCP cohort. Parameters included intra‐ and post‐operative complications, short‐term maternal/fetal outcomes, surgery duration, and delayed reconstruction in non‐IR cohort. Results: Of 82 patients with BCP, 29 (35%) had mastectomy during pregnancy: 10 (34%) had IR, 19(66%) did not. All IR utilized tissue expander (TE) placement. Mean gestational age (GA) at IR was 16.2 weeks. Mean surgery duration was 198 min with IR versus 157 min without IR. Those with IR delivered at, or close to, term infants of normal birthweight. No fetal or major obstetrical complications were seen. Post‐mastectomy radiation (PMRT) was provided after pregnancy in 2 (20%) patients in the IR cohort and 12 (63%) in the non‐IR cohort. All patients in the IR cohort successfully transitioned to permanent implant. Conclusions: This report represents one of the largest series describing IR during BCP. IR after mastectomy increased surgery duration, but was not associated with adverse obstetrical or fetal outcomes. IR with TE may preserve reconstructive options when PMRT is indicated. J. Surg. Oncol. 2016;114:140–143 . © 2016 Wiley Periodicals, Inc.